NAVIGATING EVOLVING LANDSCAPES: A PRACTICAL ANALYSIS OF ACCOUNTANT’S PROFESSIONAL COMPETENCE IN UPDATED TRENDS - Vindača, Olga; Beinarovica – Litvinova, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
As the accounting profession continues to evolve in response to technological advancements, regulatory changes, and shifting business landscapes, this article aims to explore the updated trends for accountant’s professional competence drawing parallels with practical considerations of experts within the field. Using a content analysis method, the study draws insights from a meticulously conducted questionnaire, providing a comprehensive overview of the accountant’s professional competence deemed crucial by accounting experts in navigating the dynamic challenges of today's financial environment. The findings shed light on the practical implications of accountant’s professional competence, offering valuable insights for both aspiring and seasoned professionals seeking to stay abreast of the rapidly changing trends in the accounting domain.